Influencing factors analysis of corn price fluctuation in shaanxi province, CHINA (Bangladesh Journal of Botany, 2023)
Corn is one of the most important grain crops in China, and also in Shaanxi Province. In order to master the changing law of corn market, realize reasonable regulation and control, and promote the stable development of the market, it is necessary to conduct in-depth research on the influencing factors of corn price fluctuation in Shaanxi Province. Based on the data of Shaanxi Province from 2000 to 2021, in the present study, the main factors affecting the price fluctuation in Shaanxi Province was explored by using factor analysis method. Eight indexes including corn yield, production cost, disaster-affected area, disposable income of rural residents, disposable income of urban residents, corn demand, wheat price index and consumer price were selected as factors affecting corn price fluctuation. Results showed that the disaster area and corn demand were the main factors affecting the corn price fluctuation in Shaanxi Province, and the disposable income of urban and rural residents had little impact on the corn price fluctuation. Governments and industry groups can therefore take preventive measures to limit the impact of major climate events on corn markets and economies. It also assesses the appropriate proportion of corn used for feed and energy production to ensure adequate supply and stable prices.Bangladesh J. Bot. 52(2): 607-612, 2023 (June) Special